Assessment of Immune and Oxidative Stress Biomarkers in Toxoplasmosis Patients: A Comparative Study with Healthy Controls: Penilaian Biomarker Kekebalan Tubuh dan Stres Oksidatif pada Pasien Toksoplasmosis: Sebuah Studi Perbandingan dengan Kontrol yang Sehat - Mustafa, Hamssa Majid (Universitas Muhammadiyah Sidoarjo, 2024)
Background; Toxoplasmosis, caused by the intracellular protozoan Toxoplasma gondii, is a widespread zoonotic infection that affects nearly one-third of the global population. While often asymptomatic in immunocompetent individuals, the disease can manifest severe complications in immunocompromised individuals, pregnant women, and neonates. Aims of the study; This study evaluates immune and oxidative stress biomarkers in toxoplasmosis patients to explore their role in disease severity and progression. Methodology; This study investigated biomarkers in 100 toxoplasmosis patients and 50 healthy controls, evenly divided by gender, from January 2023 to January 2024. Venous blood (5 mL) was collected, clotted, centrifuged, and serum stored at -20°C. Biomarkers measured included cytokines (IFN-γ, TNF-α, IL-10, CRP) and oxidative stress markers (MDA, SOD, CAT) using ELISA. Measurements followed manufacturer protocols, with absorbance readings taken via microplate reader. Statistical analysis assessed differences between patients and controls, with significance set at p<0.05. Results aimed to explore the role of immune and oxidative stress biomarkers in toxoplasmosis pathophysiology.Result; The study found no significant differences in demographic or lifestyle factors between Toxoplasma patients and controls, including age, gender distribution, residence, and smoking status. However, significant differences were observed in biomarker levels. Immune markers (IFN-γ, TNF-α, IL-10, and CRP) were elevated in patients compared to controls, indicating heightened immune activation. Oxidative stress markers showed contrasting trends: MDA levels were significantly higher in patients, reflecting increased lipid peroxidation, while antioxidant enzymes (SOD and CAT) were markedly lower, indicating reduced antioxidant defenses. These findings highlight the role of immune dysregulation and oxidative stress in Toxoplasma pathophysiology. Conclusions; This study highlights significant immune activation and oxidative stress in toxoplasmosis patients, with elevated inflammatory markers and reduced antioxidant enzymes. These biomarkers may serve as indicators of disease severity and progression. Highlights: Toxoplasmosis affects one-third globally, severe in immunocompromised individuals. Analyzed immune, oxidative biomarkers in 100 patients vs. 50 controls. Elevated cytokines, oxidative stress markers; reduced antioxidant enzymes in patients.. Keywords: Toxoplasmosis, immune response, cytokines, oxidative stress, biomarkers, disease progression.